Aiming for Single Digit Intraocular Pressure and Drop-Free Surgery in Glaucoma: Trabeculectomy with Mitomycin C and Intracamerular Bevacizumab - Lopes, Patrícia José Figueiredo (2022)
INTRODUCTION: Our purpose was to assess patients with single digit intraocular pressure (IOP) values and drop-free in primary trabeculectomy after using mitomycin C (MMC augmented with intracamerular bevacizumab). MÉTODOS: Retrospective, observational and comparative study. Charts from patients who underwent trabeculectomy and with IOP ≤9 mmHg at the last follow-up were included. Sub-analysis of patients screened between Oct 2015 and Mar 2019, for inclusion criteria of ≤9 mmHg at last follow-up (24 months). RESULTS: From 110 eyes screened in the initial study, 30 had the intended IOP target (MMC only: 11; MMC+bevacizumab: 19; 26% vs 41%, respectively, odds ratio 1.78, 95% IC (0.80 - 4.89), p=0.178). All these low-IOP patients were drop-free in this moment. No systemic adverse events were found and no vision-threatening complications were recorded. CONCLUSION: Adding intracamerular bevacizumab to MMC in trabeculectomy can be particularly useful in low-target IOP surgeries (such as normal tension glaucoma or very advanced glaucomas) comparing with trabeculectomy with MMC alone.